The Role of the Soyyadun Nahwi YouTube Channel in Enhancing the Understanding of Arabic Grammar (Nahwu) as an Instructional Medium in the Digital Era - Alhusna Waziadah; Ayu Mokodompit; Laili Indrayanti; Latifatussyarifah; Ima Fatimatussalika; Iwan Syafi’i (Formad English Foundation NTB-Jakarta, 2026)
The rapid development of digital technology has significantly transformed educational practices, particularly through the integration of online learning platforms. One of the most widely used digital platforms for educational purposes is YouTube, which provides accessible audio-visual learning resources that can support students’ understanding of complex subjects. In the context of Arabic language learning, the study of Arabic grammar (nahwu) is often considered challenging due to its abstract rules and complex linguistic structures. Therefore, the use of innovative digital learning media has become increasingly important in facilitating students’ comprehension of grammatical concepts. This study aimed to examine the role of the Soyyadun Nahwi YouTube Channel in enhancing students’ understanding of Arabic grammar as an instructional medium in the digital era. The research employed a qualitative descriptive approach with a case study design. The participants consisted of undergraduate students in Arabic language education programs who utilized the Soyyadun Nahwi YouTube Channel as a learning resource. Data were collected through observation, semi-structured interviews, and documentation, and were analyzed using interactive qualitative data analysis consisting of data reduction, data display, and conclusion drawing. The findings revealed that the Soyyadun Nahwi YouTube Channel significantly supported students’ understanding of Arabic grammar through structured explanations, contextual examples, and audio-visual presentations that helped clarify complex grammatical concepts. The platform also enhanced students’ motivation and engagement in learning by providing flexible access to instructional materials that could be reviewed repeatedly. These findings indicate that YouTube-based instructional media can function as an effective supplementary learning resource for Arabic grammar learning in the digital era and can support students’ independent learning practices.